The Cultural Representation in Secondary EFL Textbooks: A Critical Content Analysis and Teachersâ€™ Perceptions - Anda Roofi' Kusumaningrum; Suparno Suparno; Sumardi Sumardi (Yayasan Keluarga Guru Mandiri, 2023)
Language and culture have an inextricable relationship. The present study aims to investigate the cultural representation embodied in the Senior High School English textbooks entitled â€œBahasa Inggrisâ€ for grades 10 and 11. Moreover, this study also explores two English teachersâ€™ perceptions of the cultural representations deployed in those textbooks. Implementing qualitative critical content analysis, the study investigated the cultural point in the textbooks based on Cortazzi and Jinâ€™s (1999) cultural dimensions and Yuenâ€™s (2011) cultural aspects as the frameworks. The results show that there is an imbalanced cultural representation between three dimensions which dominantly referred to source and target cultures. In terms of cultural aspects, Products are the most aspect that appeared followed by persons. Furthermore, the teachers reported that certain cultures should be dominantly represented in textbooks. Moreover, they assumed that practices and cultural aspects should be represented more in the textbook as a way to improve the studentâ€™s attitudes. The study inferred that the textbooks failed to promote balanced cultural depiction and lack in improving studentsâ€™ intercultural awareness. This study might be useful for education stakeholders, particularly teachers to select adequate material sources; and textbook writers to re-design the ELT textbooks with various cultural diversity.